2017
DOI: 10.18203/2349-2902.isj20174879
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study of surgical treatment of pilonidal sinus; primary midline closure after elliptical excision versus rhomboid excision with limberg flap reconstruction versus open excision and healing by secondary intention

Abstract: Background: Best surgical treatment of pilonidal sinus is always challenging for a surgeon in term of recurrence. Evaluation of surgical treatment of pilonidal sinus; primary midline closure after elliptical excision versus rhomboid excision with limberg flap reconstruction versus open excision and healing by secondary intention of sacrococcygeal pilonidal disease.Methods: In this prospective randomized study of 75 patients of sacrococcygeal pilonidal sinus were divided into 3 equal groups through randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…The patients who received Limberg flap repair could return to their work after suture removal, however, patients with wide local excision resisted resuming their work due to significant anxiety about the wound and the requirement of daily dressing. In the study done by Kumar et al, the mean healing time for group II (rhomboid excision with Limberg flap reconstruction) was 17.0±8.0 days and for group III (open excision and healing by secondary intention) was 60±9.6 days which is in accordance with our findings [9]. In the present study, no recurrence was reported in either group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The patients who received Limberg flap repair could return to their work after suture removal, however, patients with wide local excision resisted resuming their work due to significant anxiety about the wound and the requirement of daily dressing. In the study done by Kumar et al, the mean healing time for group II (rhomboid excision with Limberg flap reconstruction) was 17.0±8.0 days and for group III (open excision and healing by secondary intention) was 60±9.6 days which is in accordance with our findings [9]. In the present study, no recurrence was reported in either group.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no recurrence was reported in either group. Similar results were reported by Kumar et al where none of the study participants of either group reported recurrence [ 9 ]. On contrary, Singh et al reported 16% recurrence in the wide excision group [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 10 However, challenges to incision healing include lateral tension and the potential for contamination. Although primary midline closures require less technical training and have shorter operative times, 26 28 they have also been associated with higher lateral tension and postoperative complications. 29 Data from this study suggest that the use of ciNPT may promote favorable outcomes (eg, decrease in the length of hospital stay, postoperative pain, and time-to-healing) after excision when used over closed, primary midline incisions in the intergluteal groove.…”
Section: Discussionmentioning
confidence: 99%
“…The minimally invasive approach has been named endoscopic pilonidal sinus treatment (EPSiT), adding a possible effective tool for this disease. 8,9 Despite the huge morbidity associated with pilonidal sinus disease, there is still an open debate on the optimal treatment and management associated with the best patient outcome. Hence, this study was undertaken in order to study the possible benefits and disadvantages of the EPSiT.…”
Section: Introductionmentioning
confidence: 99%